MATHEMATICAL ABILITY ANALYSIS BASED ON ASSIST SCALE WITH A DIFFERENT LEARNING APPROACH TO PREPARE A PROFESSIONAL TEACHER CANDIDATE IN DEALING WITH ASEAN ECONOMIC COMUNITY (AEC) - Sihombing, Dame Ifa; Hutauruk, Agusmanto; Husein, Ismail (UIN Sumatera Utara, 2017)
This paper aimed to basic mathematical skills based to the studying approach. To this subject pre detection is a need. One way ANOVA analyzing will show the significant of basic mathematical skill of students by giving different studying approach. Hence, there is correlation within basic mathematical skill to studying approach. Teachers should be able measure basic mathematical by designing model supporting understanding level, critical thinking ability made concept. The sample consisted of all the second semester of mathematical students by random sampling. Approaches and Study Skills Inventory for Students (ASSIST) is used to studying approach, Bayesian Information Criterion (BIC) is used to create group classification. Two Step Cluster Analysis Method divided into three approaches (Strategies, Surface, Deep)